Anterior quadratus lumborum block does not reduce postoperative opioid consumption following laparoscopic hemicolectomy: a randomized, double-blind, controlled trial in an ERAS setting. Issue 1 (27th September 2022) - Tanggaard, Katrine; Hasselager, Rune Petring; Hølmich, Emma Rosenkrantz; Hansen, Christian; Dam, Mette; Poulsen, Troels Dirch; Bærentzen, Finn Østergård; Eriksen, Jens Ravn; Gögenur, Ismail; Børglum, Jens
Abstract : Background and aims: An opioid-sparing postoperative analgesic regimen following laparoscopic hemicolectomy is optimal to promote minimal postoperative pain, early mobilization, and improved quality of recovery. Various regional anesthesia techniques have been tested to improve postoperative pain management after laparoscopic hemicolectomy. In this study, we aimed to assess the effect of administering a preoperative bilateral ultrasound-guided anterior quadratus lumborum nerve block on postoperative opioid consumption after laparoscopic colon cancer surgery. Methods: In this randomized, controlled, double-blinded trial, 69 patients undergoing laparoscopic hemicolectomy due to colon cancer were randomized to receive an anterior quadratus lumborum block with ropivacaine 0.375% 30 mL on each side or isotonic saline (placebo). The primary outcome measure was total opioid consumption during the first 24 hours postsurgery. The secondary outcome measures were pain scores, accumulated opioid consumption in 6-hour intervals, nausea and vomiting, ability of postoperative ambulation, time to first opioid, orthostatic hypotension or intolerance, postoperative Quality of Recovery-15 scores, surgical complications, length of hospital stay, and adverse events. Results: The total opioid consumption in the first 24 hours postsurgery was not significantly reduced in the ropivacaine group compared with the saline group (mean 129 mg (SD 88.4) vs mean 127.2 mg (SD 89.9), p=0.93). In addition, no secondary outcome measures showed any statistically significant intergroup differences. Conclusion: The administration of a preoperative bilateral anterior quadratus lumborum nerve block as part of a multimodal analgesic regimen for laparoscopic hemicolectomy did not significantly reduce opioid consumption 24 hours postsurgery. Trial registration number NCT03570541 .